A hydrogen-sensitive material and hydrogen sensor of titanium dioxide quantum dots modified with tin dioxide, and preparation method and application thereof

The tin dioxide nanosheets were prepared by improved solvent thermal reaction method and the calcination method to form TiO2QDs-SnO2 composite material, which solved the high cost and complex operation problems of detecting hydrogen in transformer oil in the prior art, realized the development of high-performance hydrogen sensors, and had ultra-fast response and high-precision detection capabilities.

CN116735675BActive Publication Date: 2025-04-22CHINA UNIV OF PETROLEUM (EAST CHINA)
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310240375.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-14
Publication Date
2025-04-22
Estimated Expiration
2043-03-14

AI Technical Summary

Technical Problem

The prior art has problems such as high cost, complex operation and unsuitable for large-scale, integrated applications when detecting hydrogen dissolving in transformer oil.

Method used

Titanium dioxide quantum dots were prepared by the modified solvothermal reaction method, and tin dioxide nanosheets were prepared by calcining to form TiO2QDs-SnO2 composite material as hydrogen-sensitive material. In combination with spin coating, a high-performance hydrogen sensor was prepared.

Benefits of technology

It realizes ultra-fast response and high-precision detection of dissolved hydrogen in transformer oil. The sensor has fast response/recovery time, large-scale concentration detection capabilities, excellent repeatability and selectivity, and the detection limit meets the requirements of China's power industry standard DL/T 722.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116735675B_ABST
    Figure CN116735675B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of semiconductor gas sensors, and specifically to a hydrogen-sensitive material and a hydrogen sensor of titanium dioxide quantum dots modified with tin dioxide, and a preparation method and application thereof. A SnO2 nanosheet composite material modified with TiO2 quantum dots is synthesized by combining a calcination method and an improved solvent thermal reaction method, and the SnO2 nanosheet and the TiO2 quantum dots have an n-n homojunction effect. The titanium dioxide quantum dots prepared by the improved solvent thermal reaction method have high purity, good uniformity, low synthesis temperature, easy-to-control reaction conditions, relatively simple preparation process, and no need for special expensive instruments. The TiO2QDs-SnO2 hydrogen sensor based on the titanium dioxide quantum dots has a wide detection range, ultrafast response / recovery time, excellent repeated response characteristics and selectivity, and can realize rapid and effective detection of hydrogen dissolved in transformer oil. TiO2 quantum dots have a significant effect on improving the sensing performance of TiO2QDs-SnO2 composite materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of semiconductor gas sensors, and in particular to a hydrogen-sensitive material of titanium dioxide quantum dots modified with tin dioxide and a hydrogen sensor, as well as a preparation method and application thereof. Background Art

[0002] Titanium dioxide (TiO2) is a wide-bandgap n-type semiconductor with high thermal and chemical stability. However, TiO2 with large particle size is usually insensitive to certain gases or the response / recovery speed is not fast enough, so reducing the TiO2 particle size is an effective way to improve sensor performance. Some methods for preparing TiO2 quantum dots include solid phase method, sol-gel method, hydrolysis-precipitation method, liquid phase deposition method, hydrothermal deposition method, magnetron sputtering method, ion beam enhanced deposition method, vacuum evaporation method, chemical vapor deposition method, self-assembly method and other methods. For example, the main advantages of the solid phase method are: economic, simple process and equipment, but high energy consumption; and the solid phase reaction is not sufficient, so the purity of the product cannot be well guaranteed. In addition, since the solid phase method generally requires high-temperature calcination, the product obtained is generally large in particle size and unevenly distributed. Therefore, the solid phase method is only suitable for situations where the purity and particle size of the product are not high. Compared with other methods, the solvothermal reaction method for preparing TiO2 quantum dots has the advantages of high purity, good uniformity, low synthesis temperature, easy to control reaction conditions, relatively simple preparation process, and no need for special and expensive instruments.

[0003] Oil-immersed power transformers are one of the key devices for voltage conversion in power transmission. The working state of the transformer is of great significance to the safe, stable and reliable operation of the entire power system. When thermal and electrical faults occur in the transformer, the transformer oil degrades and then produces combustible gases such as hydrogen (H2), ethylene (C2H4), acetylene (C2H2), methane (CH4) and ethane (C2H6). In the mixed gases of different components produced by different fault types of the transformer, there will be a certain amount of hydrogen as a sign. Hydrogen has been proven to be one of the key characteristic gases reflecting overheating and discharge faults of oil-immersed transformers, and it is also one of the key indicators of dissolved gas analysis (DGA). At present, there are many methods for detecting dissolved hydrogen in transformer oil in actual engineering applications, including gas chromatography, photoacoustic spectroscopy and infrared spectroscopy, but these methods require high-precision instrument support or high operating requirements, high cost and need to be carried out in a fixed test environment, which is not conducive to large-scale and integrated applications. In summary, it is of great significance to develop a high-performance hydrogen detection sensor for the monitoring of dissolved gas in transformer oil.

[0004] Gas sensors based on semiconductor metal oxides can effectively and quickly respond to target gases and have been successfully and widely used in different fields. Semiconductor metal oxide-based sensors have received widespread attention in the analysis of dissolved gases in transformer oil due to their significant advantages such as simple preparation process, low maintenance cost and long service life. SnO2, as a typical n-type semiconductor metal oxide, is widely used in gas sensors due to its wide band gap (3.6eV), ultra-high electron mobility, and extremely strong thermal stability and chemical stability. Among them, SnO2 nanosheets prepared by calcination method have attracted widespread attention due to their simple preparation, large specific surface area and good sensing performance. In recent years, in order to break through the limitations of traditional semiconductor materials in sensor applications, titanium dioxide quantum dot materials with different structures have been widely studied. At the same time, the wide band gap tunability and small size of quantum dots have also aroused great interest. The large specific surface area and carrier characteristics of titanium dioxide quantum dots can increase the active sites on the surface of sensitive materials, promote the formation of oxygen adsorbed on the surface of materials, and improve the carrier mobility characteristics of materials, thereby improving the gas sensing properties of base materials. At the same time, because of its relatively simple preparation method, the preparation of titanium dioxide quantum dots and its application in gas-sensitive detection have developed rapidly.

[0005] Density functional theory (DFT) is a method for studying the electronic structure of multi-electron systems. Through DFT, we can establish the microstructure model of the surface of sensitive materials and the target gas molecule model, simulate the adsorption process of gas molecules on the surface of sensitive materials, and analyze the interaction or reaction process between the target gas molecules and the surface of sensitive materials. Using DFT, we can propose a reasonable explanation for the improvement of TiO2QDs-SnO2 performance by modifying TiO2 quantum dots, and further verify the excellent performance of TiO2QDs-SnO2 hydrogen sensors. Summary of the invention

[0006] In view of the deficiencies in the prior art, the present invention provides a hydrogen-sensitive material and a hydrogen sensor of titanium dioxide quantum dots modified with tin dioxide, and a preparation method and application thereof. The titanium dioxide quantum dots are prepared by an improved solvent thermal reaction method, and the preparation purity and uniformity are improved, the synthesis temperature is reduced, and the reaction conditions and the preparation process are simplified. The defects of the detection method of dissolved hydrogen in transformer oil are overcome, and a sensor with TiO2QDs-SnO2 as a sensor sensitive film material and a resistance output signal is established, which has an ultra-fast response to dissolved hydrogen in transformer oil, and the TiO2 quantum dots have a significant improvement effect on the sensing performance of the TiO2QDs-SnO2 composite material. The oxygen adsorption theory of semiconductor sensors is used to explain the sensitization effect of TiO2 quantum dots and the improvement effect of the homojunction effect formed between TiO2 quantum dots and SnO2 on the sensor performance.

[0007] In order to achieve the above object, the present invention specifically adopts the following technical solutions:

[0008] A hydrogen-sensitive material of tin dioxide modified by titanium dioxide quantum dots is synthesized by combining a calcination method with an improved solvent thermal reaction method to synthesize a SnO2 nanosheet composite material modified by TiO2 quantum dots. The SnO2 nanosheet and the TiO2 quantum dots have a nn homojunction effect. The diameter of the SnO2 nanosheet is 30 to 50 nm, and the diameter of the TiO2 quantum dots is 5 nm.

[0009] A method for preparing a hydrogen-sensitive material of titanium dioxide quantum dots modified with tin dioxide comprises the following steps:

[0010] (1) Preparation of titanium dioxide quantum dots by improved solvothermal reaction method;

[0011] (2) Preparation of SnO2 nanosheets by calcination method;

[0012] (3) SnO2 nanosheets and TiO2 quantum dots are mixed to prepare TiO2QDs-SnO2 hydrogen-sensitive materials.

[0013] Further, the specific steps include:

[0014] (1) Preparation of titanium dioxide quantum dots by improved solvothermal reaction method;

[0015] ① Mix cyclohexane and anhydrous ethanol and stir them magnetically to obtain a mixed solvent, transfer the mixed solvent into a three-necked flask and equip it with a spherical condenser, quickly add tetrabutyl titanate into the three-necked flask and stir it magnetically for 30 minutes, then add hydrochloric acid into the three-necked flask to obtain a mixed solution;

[0016] ② Stir the mixed solution obtained in ① in a water bath at 70℃ for 12h;

[0017] ③ Add 200 mL of anhydrous ethanol to the white solution obtained in ② and stir until the solution turns white and then cool to room temperature with stirring;

[0018] ④ Wash the white product obtained in ③ with ethanol and dry it to obtain TiO2 quantum dots;

[0019] (2) Preparation of SnO2 nanosheets by calcination method;

[0020] Weigh SnCl4·5H2O powder and place it in a tubular calcining furnace and calcine it at 800℃ under air circulation for 4h to obtain SnO2 nanosheets;

[0021] (3) SnO2 nanosheets and TiO2 quantum dots are mixed to prepare TiO2QDs-SnO2 hydrogen-sensitive materials.

[0022] SnO2 and TiO2 quantum dots are weighed in a certain mass ratio, the two products are dissolved in an appropriate amount of anhydrous ethanol, and stirred in a 60° C. water bath for 12 hours to obtain the TiO2QDs-SnO2 hydrogen-sensitive material.

[0023] Furthermore, the volume ratio of cyclohexane, anhydrous ethanol, tetrabutyl titanate and hydrochloric acid in ① is 15:15:9:4.

[0024] Furthermore, the number of washing with anhydrous ethanol in step ④ is 6 times, the drying temperature is 60° C., and the drying time is 24 hours.

[0025] Furthermore, the heating rate of the tubular calcining furnace in (2) is 5°C / min.

[0026] Furthermore, the mass of the TiO2 quantum dots in (3) is 1wt% of the mass of the SnO2 nanosheets.

[0027] A hydrogen sensor of titanium dioxide quantum dots modified with tin dioxide, wherein the sensor is provided with a gas-sensitive coating, and the gas-sensitive coating is attached to the surface of the ceramic plate electrode of the sensor;

[0028] The preparation method of the sensor comprises:

[0029] The TiO2QDs-SnO2 hydrogen-sensitive material was added to an appropriate amount of anhydrous ethanol and ultrasonically vibrated for 10 minutes to obtain a homogeneous solution. An appropriate amount of the homogeneous solution was transferred and dropped onto the surface of the silver electrode of the ceramic plate. The TiO2QDs-SnO2 composite hydrogen-sensitive material was evenly coated on the surface of the silver electrode of the ceramic plate using a spin coater, and the solution was dried in a drying oven at room temperature of 25°C to prepare a hydrogen sensor.

[0030] The invention discloses an application of a hydrogen sensor of titanium dioxide quantum dots modified with tin dioxide, wherein the hydrogen sensor is used for rapid detection of hydrogen dissolved in transformer oil.

[0031] The advantages of the hydrogen-sensitive material and hydrogen sensor of titanium dioxide quantum dots modified with tin dioxide of the present invention and their preparation method and application are as follows:

[0032] (1) An improved solvothermal reaction method is proposed to prepare titanium dioxide quantum dots with a size of 5 nm, which improves the preparation purity and uniformity, reduces the synthesis temperature, and simplifies the reaction conditions and preparation process.

[0033] (2) The present invention combines a solvent thermal reaction method with a calcination method to synthesize a SnO2 nanocomposite material modified by TiO2 quantum dots, which has the characteristics of good crystallization and large specific surface area. At the same time, the homojunction formed between the TiO2 quantum dots and SnO2, the oxygen vacancies of the SnO2 nanosheets themselves, and the large number of active sites provided by the TiO2 quantum dots are conducive to improving the adsorption capacity of hydrogen.

[0034] (3) The present invention uses a spin coating method to evenly coat the TiO2QDs-SnO2 hydrogen-sensitive material on the surface of the silver electrode of the ceramic plate, and after drying at room temperature 25°C, a hydrogen sensor for gas dissolved in transformer oil with a TiO2QDs-SnO2 nanocomposite film is obtained. The sensor has a fast response / recovery time (the response / recovery time for 200ppm hydrogen is 2s / 5s), a wide range of concentration detection capabilities (4.8-5000ppm), excellent repeatability and selectivity, and a detection limit of 4.8ppm meets the requirements of the Chinese power industry standard DL / T 722, providing a feasible solution for achieving high-precision and ultra-fast detection of dissolved hydrogen in transformer oil.

[0035] (4) Based on the oxygen adsorption theory of semiconductor sensors, the sensitivity enhancement effect of TiO2 quantum dots and the homojunction effect formed between TiO2 quantum dots and SnO2 are explained to improve the sensor performance, providing theoretical support for the ultrafast response performance of the sensor. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 This is a flow chart of the preparation of TiO2 quantum dots based on the improved solvothermal reaction method in the examples;

[0037] Figure 2 The X-ray diffraction pattern of titanium dioxide quantum dots prepared by the improved solvothermal reaction method in the example;

[0038] Figure 3 This is a HR-TEM transmission photograph of titanium dioxide quantum dots prepared based on the improved solvothermal reaction method in the example;

[0039] Figure 4 It is a flow chart of sensor testing in the embodiment;

[0040] Figure 5 The X-ray diffraction pattern of the SnO2 composite hydrogen-sensitive material modified by TiO2 quantum dots in the embodiment;

[0041] Figure 6 (a) is a SEM electron microscope photo of the TiO2QDs-SnO2 composite hydrogen-sensitive material in the embodiment, and (b) is a HR-TEM transmission photo of the TiO2QDs-SnO2 composite hydrogen-sensitive material;

[0042] Figure 7 is the response curve of the sensor in the embodiment at different operating temperatures;

[0043] Figure 8 is a dynamic resistance response curve diagram of the sensor in the embodiment to different concentrations of hydrogen;

[0044] Fig. 9 is a curve diagram of the response value of the sensor in the embodiment to different concentrations of hydrogen;

[0045] Fig.10 is a fitting curve diagram of the hydrogen concentration and response value of the sensor in the embodiment;

[0046] Fig.11 2 is a graph showing the response and recovery time of the sensor in the embodiment to 200 ppm hydrogen;

[0047] Fig.12 is a reproducibility curve diagram of the sensor in the embodiment for 100, 1000, and 2000 ppm hydrogen;

[0048] Fig.13 This is a long-term stability test of the sensor in the embodiment within one month;

[0049] Fig.14 The following is a selectivity test of the sensor in the embodiment to several typical transformer oil dissolved gases. DETAILED DESCRIPTION

[0050] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0051] The test methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified.

[0052] Example 1

[0053] The preparation process of titanium dioxide quantum dots is as follows Figure 1 As shown, the specific preparation steps are as follows:

[0054] ① Mix 15 mL of cyclohexane and 15 mL of anhydrous ethanol and stir magnetically for 10 min to obtain a mixed solvent, transfer the mixed solvent to a 250 mL three-necked flask equipped with a spherical condenser. Quickly add 9 mL of tetrabutyl titanate to the three-necked flask and stir magnetically for 30 min, then add 4 mL of hydrochloric acid to the three-necked flask to obtain a mixed solution;

[0055] ② Stir the mixed solution obtained in step ① in a water bath at 70°C for 12h;

[0056] ③ Add 200 mL of anhydrous ethanol to the white solution obtained in step ② and stir until the solution turns white, then stir and cool to room temperature;

[0057] ④ Wash the white product obtained in step ③ with ethanol for 6 times and dry it in a drying oven at 60°C for 24 hours to obtain TiO2 quantum dots.

[0058] like Figure 2 The XRD spectrum of the TiO2 quantum dots of the present invention is shown. No characteristic peaks of other impurities are observed in the figure, indicating that the purity of the TiO2 quantum dots is high. According to the XRD characterization information, the theoretical diameter of the prepared TiO2 quantum dots is 10.09nm.

[0059] like Figure 3 The HR-TEM transmission photographs of the TiO2 quantum dots of the present invention are shown. The lattice spacings of the TiO2 quantum dots are and They correspond to the (004) crystal plane and (101) crystal plane in the standard card PDF#21-1272. The diameter of a single TiO2 quantum dot is 5nm.

[0060] Example 2

[0061] A sensor based on a composite material of SnO2 nanosheets modified with TiO2 quantum dots coated on the surface of a ceramic plate silver electrode, the test process diagram is as follows Figure 4 shown.

[0062] The sensor test is performed by a dynamic gas-sensitive test system, which simulates the test process of the dissolved gas analysis (DGA) method of the transformer online evaluation method. The TiO2QDs-SnO2 hydrogen-sensitive material is fully ground and evenly coated on the surface of the silver electrode of the ceramic plate by spin coating. Multiple ceramic plates are installed in a closed test chamber to form a sensor array, and the operating temperature of the array can be precisely controlled. In addition, nitrogen is used as the carrier gas of the target gas (hydrogen), and the gas concentration is controlled by the gas flow control module to complete the sensor test.

[0063] The X-ray diffraction pattern of SnO2 nanosheet composite material modified by TiO2 quantum dots is shown in Figure 5 As shown in the figure, the prepared SnO2 nanosheets correspond to the standard card PDF#99-0024 and are in good crystallization condition. After compounding with TiO2 quantum dots, the corresponding diffraction peaks of TiO2 cannot be observed because the mass ratio of TiO2 quantum dots is only 1wt% of SnO2 nanosheets, which does not reach the detection limit of XRD equipment. No impurity peaks are observed in the pure SnO2 spectrum in the figure, indicating that the purity of SnO2 is high.

[0064] Scanning electron microscopy and transmission electron microscopy images of SnO2 nanosheet composites modified by TiO2 quantum dots are shown in Figure 2. Figure 6 As shown. Figure 6In the scanning electron microscope photo (a), large polygonal SnO2 nanosheets and relatively small TiO2 nanoparticles can be observed. The diameter of the SnO2 nanosheets is 30-50nm, and the diameter of the TiO2 quantum dots is 5nm. This structure has a large specific surface area. Figure 6 The transmission electron microscopy image in (b) shows that the lattice spacing of SnO2 is Corresponding to the (110) crystal plane of SnO2; the lattice spacing of TiO2 is Corresponding to the (004) crystal plane of TiO2.

[0065] A method for preparing a SnO2 nanocomposite material and a sensor modified with TiO2 quantum dots by a solvent thermal reaction method and a calcination method is carried out according to the following steps:

[0066] ① Weigh 3.5 g SnCl4·5H2O powder and place it in a tubular calcining furnace and calcine it at 800℃ under air circulation for 4 h to obtain SnO2 nanosheets;

[0067] ② The SnO2 nanosheets and TiO2 quantum dots obtained in step ① are weighed in a certain mass ratio, the two products are dissolved in an appropriate amount of anhydrous ethanol, stirred in a 60° C. water bath for 12 h and then dried to obtain the TiO2QDs-SnO2 hydrogen-sensitive material;

[0068] ③ Add the SnO2 nanocomposite material modified by TiO2 quantum dots to an appropriate amount of anhydrous ethanol, and ultrasonically vibrate for 10 minutes to obtain a homogeneous solution; transfer an appropriate amount of the homogeneous solution to the surface of the silver electrode of the ceramic plate, and use a spin coater to evenly coat the TiO2QDs-SnO2 composite hydrogen-sensitive material on the surface of the silver electrode of the ceramic plate. Dry it in a drying oven at room temperature of 25°C to prepare a hydrogen sensor.

[0069] The test results of the optimal operating temperature of the dissolved hydrogen sensor in transformer oil based on TiO2 quantum dots modified SnO2 nanocomposite for 2000ppm hydrogen are as follows Figure 7 As shown in the figure, it can be seen that the sensor has the highest response value to 2000ppm hydrogen at 400℃ and the best sensing performance, so 400℃ is selected as the operating temperature of the sensor.

[0070] The dynamic resistance response results of the hydrogen sensor dissolved in transformer oil based on TiO2 quantum dots modified SnO2 nanocomposite materials to different concentrations of hydrogen are shown in Figure 2. Figure 8 As shown in the figure, it can be seen that the resistance response of the hydrogen sensor increases with the increase of hydrogen concentration, indicating that the hydrogen sensor based on TiO2QDs-SnO2 hydrogen-sensitive material can be used for the detection of dissolved hydrogen in a wide range of transformer oils. Fig. 9The sensor is given Figure 8 Based on this, the continuous response value calculation curve of hydrogen with gradually increasing concentration is shown.

[0071] Based on the dynamic response results of TiO2QDs-SnO2 hydrogen sensor at 20-5000ppm hydrogen concentration, Fig.10 The function fitting curve of hydrogen concentration and response value is given. As can be seen from the figure, its nonlinear fitting equation is Y = -59.33 × exp (-x / 929.34) -4.07, and the correlation coefficient is 0.95103. Based on this, it is deduced that the detection limit of the sensor is 4.8ppm, which meets the requirements of China's power industry standard DL / T 722.

[0072] Fig.11 The figure shows the response and recovery time curve of the hydrogen sensor dissolved in transformer oil based on TiO2QDs-SnO2 hydrogen-sensitive material to 200ppm hydrogen. As can be seen from the figure, the sensor has an adsorption time of 2s and a desorption time of 5s for hydrogen. This shows that after the TiO2 quantum dots and SnO2 nanosheets are composited, they have excellent response / recovery capabilities to hydrogen, which is also one of the advantages of the present invention.

[0073] Fig.12 The graph shows the reproducibility of the sensor of the present invention to 100, 1000, and 2000 ppm hydrogen. As can be seen from the graph, the sensor is exposed to three test environments with set hydrogen concentrations in sequence, and each concentration gradient is continuously cycled 3 times. The results show that the sensor has good response repeatability to different concentrations of hydrogen.

[0074] Fig.13 The long-term stability test of the sensor of the present invention is shown in the figure. It can be seen from the figure that the sensor has good response stability to various concentrations of hydrogen within 30 days.

[0075] Fig.14 The sensor of the present invention is tested for selectivity to several typical transformer oil dissolved gases. As can be seen from the figure, the sensor of the present invention has a significantly higher response capability to hydrogen (H2) than other typical transformer oil dissolved gases such as carbon monoxide (CO), methane (CH4) and ethane (C2H6), indicating high selectivity to hydrogen. Since the detection upper limit of most carbon monoxide detection equipment on the market is 30-50ppm, 2000ppm hydrogen, 50ppm carbon monoxide, 2000ppm methane and 2000ppm ethane were selected in the selectivity test to test the sensor of the present invention.

[0076] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable ordinary technicians in the field to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made based on the essence of the content of the present invention should be included in the protection scope of the present invention.

Claims

1. A hydrogen-sensitive material of titanium dioxide quantum dots modified with tin dioxide, characterized in that: A SnO2 nanosheet composite material modified by TiO2 quantum dots is synthesized by combining a calcination method and an improved solvent thermal reaction method, wherein there is a nn homojunction effect between the SnO2 nanosheet and the TiO2 quantum dots, the diameter of the SnO2 nanosheet is 30 to 50 nm, and the diameter of the TiO2 quantum dots is 5 nm; The preparation method of the hydrogen sensitive material comprises the following steps: (1) Preparation of titanium dioxide quantum dots by improved solvothermal reaction method; ① Mix cyclohexane and anhydrous ethanol and stir them magnetically to obtain a mixed solvent, transfer the mixed solvent into a three-necked flask and equip it with a spherical condenser, quickly add tetrabutyl titanate into the three-necked flask and stir it magnetically for 30 minutes, then add hydrochloric acid into the three-necked flask to obtain a mixed solution; ② Stir the mixed solution obtained in ① in a water bath at 70℃ for 12h; ③ Add 200 mL of anhydrous ethanol to the white solution obtained in ② and stir until the solution turns white and then cool to room temperature with stirring; ④ Wash the white product obtained in ③ with anhydrous ethanol and dry it to obtain TiO2 quantum dots; (2) Preparation of SnO2 nanosheets by calcination method; Weigh SnCl4·5H2O powder and place it in a tubular calcining furnace and calcine it at 800℃ under air circulation for 4h to obtain SnO2 nanosheets; (3) SnO2 nanosheets and TiO2 quantum dots were mixed to prepare TiO2 QDs-SnO2 hydrogen-sensitive materials; SnO2 and TiO2 quantum dots are weighed in a certain mass ratio, the two products are dissolved in an appropriate amount of anhydrous ethanol, and stirred in a water bath at 60° C. for 12 hours to obtain the TiO2 QDs-SnO2 hydrogen-sensitive material; The volume ratio of cyclohexane, anhydrous ethanol, tetrabutyl titanate and hydrochloric acid in ① is 15:15:9:4; The number of times of washing with anhydrous ethanol in said step ④ is 6 times, the drying temperature is 60°C, and the drying time is 24h; The heating rate of the tubular calcining furnace in (2) is 5°C / min; The mass of the TiO2 quantum dots in (3) is 1 wt% of the mass of the SnO2 nanosheets.

2. A hydrogen sensor of titanium dioxide quantum dots modified with tin dioxide, characterized in that: The sensor is provided with the hydrogen-sensitive material as claimed in claim 1, and the hydrogen-sensitive material is attached to the surface of the ceramic plate electrode of the sensor; The preparation method of the sensor comprises: The TiO2 QDs-SnO2 hydrogen-sensitive material was added to an appropriate amount of anhydrous ethanol and ultrasonically vibrated for 10 minutes to obtain a homogeneous solution. An appropriate amount of the homogeneous solution was transferred and dropped onto the surface of the silver electrode of the ceramic plate. The TiO2 QDs-SnO2 composite hydrogen-sensitive material was evenly coated on the surface of the silver electrode of the ceramic plate using a spin coater and dried in a drying oven at room temperature of 25°C to prepare a hydrogen sensor.

3. An application of the titanium dioxide quantum dot modified tin dioxide hydrogen sensor according to claim 2, characterized in that: The hydrogen sensor is used for rapid detection of hydrogen dissolved in transformer oil.